KOPRODUKSI DAN SINERGISME: PERGESERAN PARADIGMA DALAM PELAYANAN PUBLIK - Syahra, Rusydi (P2KK LIPI, 2005)
This article seeks to discuss a shift in paradigm in public service policy from full government responsibility toward the larger participation of civil society in public service provision. The dominant paradigm is that conventionally the government positions itself as the provider of services, whereas the people perceive themselves as the beneficiaries because as the tax payers they assume every right to enjoy the services. However this paradigm has been challenged by the fact that in recent development the governments in many countries have shown their inability to shoulder the full responsibility in public services and have rendered part of the responsibility to the communities. A number of studies conducted in these countries concluded that there is a tendency toward an increase in civic engagement in the forms of coproduction and synergy between the government and the communities in service provision. Recent government policies in several municipalities in Brazil that allow citizens’ participation in the planning, budgeting, implementing and monitoring many kinds of public services are provided as an example to show that a new paradigm is being adopted to replace the old one. In Indonesia, despite a longtime recognition of community participation in development in the form of swadaya masyarakat or community contribution in development, in most instances the government still perceives itself as the sole benefactor of public services. Some structural and cultural problems must be addressed before the new paradigm can be fully adopted in this country.